Manufacturing and Performance of an Economical 1-D Shake Table - Aamar Danish; Naveed Ahmad; M. Usama Salim (Civil Engineering Journal, 2019)
The researchers and engineers encountered many problems to precisely replicate earthquake waves. Earthquakes are one of the nature's worst catastrophes and are still unpredictable. Statistical research has shown that the earthquakes have increased in frequency in recent years and have become a major concern for the world especially for those countries which are located on the fault lines such as Japan, Bangladesh and Pakistan. So, it was imperative to device a mechanism to check earthquake response and apply some necessary mitigations for the safety of humanity. After many years of research an indispensable testing apparatus was designed named as Shake Table. This apparatus is extensively used in earthquake research centers globally because it is the best available apparatus to replicate the earthquakes imposed dynamic effects on structures. A uni-axial shaking table was designed, manufactured and installed in University of Engineering & Technology Taxila, Pakistan which is operated on 3 HP servo motor coupled with encoder, motion controller and supported on HSB mechanical linear drive. The system was assembled in a simple way with care to endure sufficient replication of given (recorded) motion by shake table system. This paper focuses on the designing, manufacturing and performance of an economical analytical model of 1-D shake table incorporating conjunction of structural dynamics and linear control theory.